2019
DOI: 10.1158/1078-0432.ccr-18-0179
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Promoter Methylation Is Linked to Defective Homologous Recombination Repair and Elevated miR-155 to Disrupt Myeloid Differentiation in Myeloid Malignancies

Abstract: Purpose: Defective homologous recombination (HR) has been reported in multiple myeloid disorders, suggesting a shared dysregulated pathway in these diverse malignancies. Because targeting HR-defective cancers with PARP inhibition (PARPi) has yielded clinical benefit, improved understanding of HR defects is needed to implement this treatment modality.Experimental Design: We used an ex vivo irradiation-based assay to evaluate HR repair, HR gene promoter methylation, and mRNA expression in primary myeloid neoplas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Loss of BRCA activity can occur by somatic or germline mutation, loss of heterozygosity, copy number alterations (regional or whole chromosome alterations or deletions), or promoter methylation with gene silencing [59,60]. Multiple investigators have demonstrated that BRCA gene silencing via hypermethylation occurs not only in AML but also in multiple solid tumors, including breast, ovary, and prostate cancer [56,57,[59][60][61][62][63][64]. In addition, hypermethylation has been reported as a consequence of both cytotoxic chemotherapy and radiation [58].…”
Section: Hrd and T-mds/amlmentioning
confidence: 99%
“…Loss of BRCA activity can occur by somatic or germline mutation, loss of heterozygosity, copy number alterations (regional or whole chromosome alterations or deletions), or promoter methylation with gene silencing [59,60]. Multiple investigators have demonstrated that BRCA gene silencing via hypermethylation occurs not only in AML but also in multiple solid tumors, including breast, ovary, and prostate cancer [56,57,[59][60][61][62][63][64]. In addition, hypermethylation has been reported as a consequence of both cytotoxic chemotherapy and radiation [58].…”
Section: Hrd and T-mds/amlmentioning
confidence: 99%
“…Here, we presented HAI-1 promoter hypomethylation in a proportion of HCC patients and linked expression upregulation. Built upon the several published whole-genome bisulfite analysis studies which described that methylation alterations play a role in inhibiting differentiation in hematopoietic malignancies [44, 45], we did observe that this epigenetic change in HAI-1 contributes reduced differentiation ability in this retrospective HCC case cohort. While data in the current study provided some evidence, the association between the promoter methylation level of HAI-1 and HCC differentiation status needs to be further confirmed in a larger patient cohort.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have shown a close link between low expression of BRCA1 and its promoter methylation. 20 Previous studies showed that BRCA1 promoter methylation was observed in about 20%–60% of TNBC patients. 8,21,22 The methylation status of BRCA1 is significantly correlated with the co-expression of DNMTs.…”
Section: Resultsmentioning
confidence: 99%
“…Low expression of BRCA1 is closely related to its promoter methylation. 20 Flavonoids can affect DNA methylation and genome stability. 33,34 Moreover, DNMT can affect the expression of BRCA1.…”
Section: Discussionmentioning
confidence: 99%